Influence of increased doses of fenbendazole supramolecular complex on sheep’s organism - A. I. Varlamova (Российский паразитологический журнал, 2019)
The purpose of the research: study of the influence of increased doses of fenbendazole supramolecular complex (FSMC) on sheep’s organism. Materials and methods. The experiment was carried out at the Podolsk Department of All-Russian Scientific Research Institute of Fundamental and Applied Parasitology of Animals and Plants named after K. I. Skryabin on 20 manorial invasion-free sheep aged 2-3 years old. Animals were divided according to the principle of analogues into 4 groups, 5 heads in each group. Animals of the 1, 2 and 3 group were orally administered with FSMC given as a single dose of 2, 6, 10 mg/kg, respectively, according to the active substance, i.e in therapeutic and in a dose increased by 3 and 5 times. Sheep of the fourth group didn’t receive the drug and they were as control. Study of clinical, hematological and biochemical parameters of animals from all groups was conducted 1 day before and in 1, 3, 5 days after administration of the drug by means of standard methods. Results and discussion. FSMC in therapeutic dose as well as in a dose increased by 3 and 5 times doesn’t have negative influence on clinical, hematological and biochemical parameters of the sheep. State of the sheep, which received the drug in doses of 20, 60, 100 mg/kg, was within the physiologically normal state and didn’t differ from the state before administration of the drug and from the animals of the control group. Drug security index exceeds 5. Red blood cell count, white blood cell count, hemoglobin count, leukogram parameters as well as biochemical parameters of blood: activity of alkaline phosphatase and amylase, bilirubin, creatinine, urea and glucose counts were within normal limits and didn’t differ from the parameters of the control animals.